Omvårdnad vid blodprovstagning och venpunktion på fåglar - Knutsson, Linn (2014)
Blood sampling is one of the most important diagnostic tools in veterinary medicine, and this is also true for avian medicine. A properly collected and handled venous sample can be used for serology, biochemistry and electrolyte analysis, as well as for blood smears, packed cell volume and cell differentiation. Caring for sick birds is a challenge for all veterinary staff. Many birds are easily stressed individuals, and to a very ill bird a big increase in stress level can even be fatal. Avian patients who are presented in a veterinary clinic are often in a poor condition, and blood sampling is an invasive procedure that can cause stress to the patient. Stress is also detrimental to the blood test results as it can alter the values of some blood components, making the results less reliable.